Decreased moment of inertia of the lower limb facilitates a rapid hip internal rotation in a simulated foot impact maneuver. A laboratory-controlled biomechanical study for a precursor mechanism of noncontact anterior cruciate ligament injury - Arita, K.; Ogasawara, I.; Konda, S.; Matsuo, T.; Uno, Y.; Yoshida, N.; Zhang, X.; Nishizawa, I.; Liu, J.; Nakata, K. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Anterior cruciate ligament injury frequently occurs in the deceleration with the knee-extended position. In addition, a rapid hip internal rotation is concomitantly observed. However, how the extended knee position induces the hip internal rotation is unclear. METHODS: Sixteen healthy participants performed the simulated foot impact task on the experimental chair. To vary the knee flexion angle, the following four-foot placement positions relative to the pelvis segment, i.e.: 1) near; 2) middle; 3) far; and 4) far + heel strike, were tested. The reflective marker positions and the ground reaction force (GRF) data were collected. The moment of inertia of the entire lower limb around its long axis as well as the peak hip internal rotation angular velocity were calculated and compared among four conditions (Wilcoxon Signed-Rank Test with Bonferroni correction, P<0.0083). RESULTS: As the knee extended from the near to far + heel strike condition, the moment of inertia of the entire lower limb significantly decreased and hip internal rotation angular velocity significantly increased (P<0.001). CONCLUSIONS: The extended knee position with far foot placement from torso reduces the inertial resistance of the entire lower limb around its long axis and is vulnerable to the hip internal rotation.